Ethiopia Economic Update, No. 8 : Ensuring Resilient Recovery from COVID-19 - Sanchez Martin, Miguel; Mulugeta, Samuel; Getachew, Zerihun; Wieser, Christina (World Bank, Washington, DC, 2021)
COVID-19 has severely affected Ethiopia, weakening its economic performance. Ethiopia has experienced a collapse in external demand since April 2020 due to COVID-19. While merchandise exports, excluding gold, increased by 5.8 percent overall in FY20, they declined by 4.1 percent during July-December 2020 (year-on-year). Exports of garments, textiles, and fruits and vegetables have been particularly hit since the onset of the pandemic. Both exports and imports of services, dominated by air transport, recorded negative growth in FY20. Remittances dropped by 10 percent in FY20, although they have rebounded during the first half of FY21. Merchandise imports, which were already on decline prior to COVID-19, dropped by 8 percent in FY20, contributing to the narrowing of the current account balance, estimated at about 4 percent of GDP. Meanwhile, foreign direct investment has been severely hit, with inflows declining by 20 percent in FY20, contributing to weakening reserve levels. Despite the severe impacts, Ethiopia grew at 6.1 percent in FY20, as the impact of the COVID-19 pandemic took place largely in the final quarter of the fiscal year. Phone survey data suggests that both firm revenue and household income are significantly depressed, which points to weakening domestic demand. The adverse impact of the COVID-19 pandemic on economic activity is expected to continue in FY21, prior to experiencing a rebound in FY22 and beyond. Further action is needed to ensure a resilient economic recovery. The Government of Ethiopia is to be commended for having kept advancing its Homegrown Economic Reform Agenda despite COVID-19. Implementing some complementary reforms will be key to ensuring a resilient recovery in the new COVID-19 normal.